#### Answer

$(3x+2)(2x-5)$

#### Work Step by Step

$6x^{2}−11x−10 $
First, identify two numbers that multiply with each other to become -60, the product of the constant and coefficient of $x^{2}$ (6 × -10) and add together to become -11, the coefficient of x.
From inspection, we identify these numbers as 4 and -15.
Secondly split the coefficient of x into the sum of the two above numbers.
$6x^{2}−11x−10 $
$=6x^{2}+(4-15)x−10 $
$=6x^{2}+4x-15x−10 $
Factorize by grouping to find the answer.
$6x^{2}+4x-15x−10 $
$=2x(3x+2)-5(3x+2) $
$=(3x+2)(2x-5)$